O desempenho dos fornecedores influência nos resultados dos indicadores de continuidade de uma distribuidora de energia elétrica? - Gomes , Luciana (2021)
Objective of the work: This paper aims to investigate, through a qualitative approach, the relationship between the performance of maintenance/works service providers in distribution networks and the result of the collective continuity indicator – DEC – of an electricity distributor. Design / Methodology / Approach: This research is a case study in which the objective is to evaluate the relationship between the performance of suppliers and the performance of the distributor. For this, the purchasing segment of the services area was chosen, with the highest net value contracted by the distributor. For the evaluation of the data, the qualitative method with content analysis of semi-structured interviews with CEMIG's contract managers and suppliers was applied. Results: According to our findings, there is evidence of: (i) the existence of collaboration in the buyer-supplier relationship; (ii) existence of the relationship between the performance of the supplier and the buyer due to the buyer's dependence on its suppliers; (iii) the suppliers' indicators are associated with the distributor's performance measures, which allows for more assertive decision-making and (iv) supply interruptions negatively affect the distributor's results due to the high dependence on the supply of services from the suppliers. Based on these results, there is evidence that the performance of suppliers affects the results of the collective continuity indicator – DEC – of the distributor. Practical Implications: This work has practical implications for: (i) the electricity distribution sector, as it shows that the performance of the buyer-supplier relationship can affect the strategic results of the distributors, (ii) business sectors that are highly dependent on their suppliers, as their results will also depend on the performance of their suppliers. Originality and Contributions: The performance in the buyer-supplier relationship is much discussed in the literature. However, in the Brazilian electricity distribution sector there was a lack of studies that addressed the management of the supply chain and its performance. The originality of this work is to unite, in a single study related to the electricity sector, through a qualitative approach, the relationship of the sector with its suppliers, considering the management of the supply chain, the performance of the buyer-supplier relationship, the measurement performance through non-financial indicators and the risk associated with the contracted object. As a contribution, this study suggests that good supply chain management with defined performance metrics and linked to the distributor's results, considering the risks of the buyer-supplier relationship, can bring gains for the distributor, its suppliers and its customers and consumers, because achieving better results, all actors in this relationship will benefit.